2018
DOI: 10.1111/aos.13830
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of intraocular inflammation following standard or heavy silicone oil tamponade: a prospective study

Abstract: Although both HSO and PDMS yielded favourable success rates in the surgical treatment of complicated retinal detachments, HSO triggered a more severe inflammatory reaction, in a time-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…Previous studies have reported that the use of Densiron ® 68 results in higher IOP levels, and more cases of inflammatory reaction and emulsification than Oxane ® HD because of its lower viscosity (1400 cSt for Densiron ® 68 vs. 3300 cSt for Oxane ® HD at 25°C. 26,27,28 Nevertheless, in our study Densiron ® 68 and Oxane ® HD had similar, low complication rates. Two steps of the procedure could explain these low complication rates: first, all patients received a subconjunctival injection of 4 mg dexamethasone at the end of surgery, which reduces postoperative inflammation, and second, the ocular cavity was completely filled with HDSO.…”
Section: Discussionsupporting
confidence: 42%
“…Previous studies have reported that the use of Densiron ® 68 results in higher IOP levels, and more cases of inflammatory reaction and emulsification than Oxane ® HD because of its lower viscosity (1400 cSt for Densiron ® 68 vs. 3300 cSt for Oxane ® HD at 25°C. 26,27,28 Nevertheless, in our study Densiron ® 68 and Oxane ® HD had similar, low complication rates. Two steps of the procedure could explain these low complication rates: first, all patients received a subconjunctival injection of 4 mg dexamethasone at the end of surgery, which reduces postoperative inflammation, and second, the ocular cavity was completely filled with HDSO.…”
Section: Discussionsupporting
confidence: 42%
“…SO unleashes a foreign body-like reaction in the trabecular meshwork with SO microbubbles phagocytized by macrophages [ 67 , 68 , 69 , 70 , 71 , 72 ]. Heavy SO (HSO) may result in a higher inflammatory reaction, probably due to its increased emulsification tendency compared to PDMS [ 73 , 74 ]. These etiological pathways lead to an open angle mechanism that underlies OH and is usually managed medically [ 2 , 4 , 37 ].…”
Section: Early Post-operative Ocular Hypertensionmentioning
confidence: 99%
“…Ocular inflammation is one of the factors involved in IOP elevation during silicone oil endotamponade [ 74 ]. Although in some studies inflammation rate seems to be proportional to the duration of tamponade application [ 4 , 74 , 100 ], evidence suggests that this reaction may likely persist after SO removal and may contribute to the IOP rise [ 101 , 102 ]. Percentages of ocular inflammation described in the literature range from 3 to 41% within 4 months from silicone oil injection [ 103 ].…”
Section: Late Onset Silicone Oil-induced Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to improve the healing of the underlying retinal tears, there are two heavy silicone oil products approved as intraocular tamponades for clinical use in Europe, Oxane HD (siliconefluorinated paraffin mixture) and Densiron (silicone-heavy water mixture) [2] . Heavy silicone oil solves the problem of the lower retinal detachment in some extent and help for the retina reattachment, whereas many of its complications have also been observed in clinical applications, such as cataract, intraocular light-to-moderate inflammatory response and increased intraocular pressure, etc [3] .Therefore, vitreous tamponades with good biocompatibility, stable properties, and no recipient limitation, should be developed to effectively press the retinal tears with different orientations [4] .…”
Section: Introductionmentioning
confidence: 99%